الاختيارات الفقهية في حاشية ابن عابدين جزء من كتاب القضاء وأثرها في القانون الأردني دراسة تطبيقية مقارنة: Preferred Legal Pinions in the Chapter of Judgeship of Ḥāshiyat Ibn-i ‘Ābidīn and Their Impact on Jordanian Law: An Applied and Comparative Study - يسرى أحمد عبدالحافظ (الدراسات الإسلامية, 2022)
This study aims to examine the opinions preferred by the Syrian jurist Ibn-i-‘Ābidīn (d.1836/1252) in his book Radd al-Muḥtār out of the various opinions in the Ḥanafī school of law. Radd al-Muḥtār is an important source of the Ḥanafī school of law that is heavily relied upon in the discipline of the fatwā writing because its author meticulously studied the primary sources to verify the authenticity of jurisprudential views recorded in the later sources of the Ḥanafī school of law and corrected them whenever he found them incorrect. The Book of Judgement (Kitāb al-Qaḍā’) has been selected from Radd al-Muḥtār to analyze the legal reasoning and causes that led Ibn-i ‘Ābidīn to prefer certain opinions and reject others. This research work also undertakes a comparative study of Jordanian law with the opinions adopted by Ibn-i ‘Ābidīn and examines the compatibility of the former with the latter.